Dual PDF Signaling Pathways Reset Clocks Via TIMELESS and Acutely Excite Target Neurons to Control Circadian Behavior. - Seluzicki, A.; Flourakis, M.; Kula-Eversole, E.; Zhang, L.; Kilman, V.; Allada, R. (PLoS Biology, 2014)
Molecular circadian clocks are interconnected via neural networks. In Drosophila, PIGMENT-DISPERSING FACTOR (PDF) acts as a master network regulator with dual functions in synchronizing molecular oscillations between disparate PDF(+) and PDF(-) circadian pacemaker neurons and controlling pacemaker neuron output. Yet the mechanisms by which PDF functions are not clear. We demonstrate that genetic inhibition of protein kinase A (PKA) in PDF(-) clock neurons can phenocopy PDF mutants while activated PKA can partially rescue PDF receptor mutants. PKA subunit transcripts are also under clock control in non-PDF DN1p neurons. To address the core clock target of PDF, we rescued per in PDF neurons of arrhythmic per?¹ mutants. PDF neuron rescue induced high amplitude rhythms in the clock component TIMELESS (TIM) in per-less DN1p neurons. Complete loss of PDF or PKA inhibition also results in reduced TIM levels in non-PDF neurons of per?¹ flies. To address how PDF impacts pacemaker neuron output, we focally applied PDF to DN1p neurons and found that it acutely depolarizes and increases firing rates of DN1p neurons. Surprisingly, these effects are reduced in the presence of an adenylate cyclase inhibitor, yet persist in the presence of PKA inhibition. We have provided evidence for a signaling mechanism (PKA) and a molecular target (TIM) by which PDF resets and synchronizes clocks and demonstrates an acute direct excitatory effect of PDF on target neurons to control neuronal output. The identification of TIM as a target of PDF signaling suggests it is a multimodal integrator of cell autonomous clock, environmental light, and neural network signaling. Moreover, these data reveal a bifurcation of PKA-dependent clock effects and PKA-independent output effects. Taken together, our results provide a molecular and cellular basis for the dual functions of PDF in clock resetting and pacemaker output.